Application of Bankruptcy Provisions to Condominium HT Objects and their Relation to the Binding Power of Preferent Rights Under the Bankruptcy Law - Aslan Noor; Anik Istiqomah; Hermindo Hermindo; Nurfarida Nurfarida; Attansya Rafli Rusaedi (Lambung Mangkurat Law Journal, 2024)
This research examines the application of bankruptcy provisions to condominium Mortgage Rights (HT) objects and their relationship with the binding power of preference rights based on the Bankruptcy Law. Condominiums as a unique form of property ownership, with the characteristics of joint shares, joint objects, and joint land, create their complexities when faced with a bankruptcy situation. This research uses normative juridical methods with statutory and conceptual approaches to analyze these problems. The research results show that the application of bankruptcy provisions to condominium HT objects has several specificities. First, the curator must make a clear separation between the bankruptcy assets which are part of the individual apartment units and the common parts, joint objects and joint land. Second, the bankruptcy process and HT execution must still pay attention to the rights of other residents in the condominium, as regulated in the Condominium Law. Third, intensive coordination is required between the curator and the Association of Owners and Residents of Flats (PPPSRS) in the bankruptcy process. Regarding the binding power of preferential rights, this research found that the preferred rights of creditors of condominium HT holders are still recognized in the bankruptcy process as regulated in Article 55 paragraph (1) of the Bankruptcy Law. However, its implementation has several limitations and special considerations. HT execution only can done to part unit House individual arrangement, not including part together, thing together, and land together. Additionally, fulfillment​ obligations to PPPSRS, such as dues management and maintenance, must prioritized For guard continuity function condo. Study This conclusion required harmonization between the Bankruptcy Law, the Mortgage Law, and the Condominium Law to give certainty law for all parties involved​ in the case of bankruptcy condominium HT object. Proposed recommendations​ cover preparation rules for more implementers​ Specifically about mechanism bankruptcy condominium HT objects and improvements in coordination between institutions related to handling cases similar.